SISTEM PENDIDIKAN DI NEGARA AUSTRALIA - Abdul Wahab Syakhrani; Ahmad Fauzi, Ahmad Syaifullah, Muhammad Idris, Muhammad Rif’an (CV. ADIBA ASIHA AMIRA, 2022)
Explaining can be interpreted as an effort to organize the lesson content in a planned order so that it is easily understood by students. Submission of information that is well planned and presented in an appropriate sequence is the main characteristic of explaining activities. Broadly speaking, the components of explaining skills are divided into two, namely first, analyzing and planning and second, presenting. Things that need to be considered in analyzing and planning, namely: the content of the message (material) to be conveyed and students as message recipients. Asking skill is the teacher's skill in asking questions as part of stimulating students to respond to the lesson material that is being or has been studied. Several functions of questions: 1) Arouse students' interest and curiosity about a topic; 2) Focus on a particular problem; 3) Stimulating students to ask their own questions; 4) Diagnosing student learning difficulties; and 5) Provide opportunities for learning discussions